2019
DOI: 10.22146/ijc.36706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Time and Diimide/Rubber Ratio on the Hydrogenation of Liquid Natural Rubber by Response Surface Methodology

Abstract: Hydrogenated liquid natural rubber (HLNR) was synthesized from liquid natural rubber (LNR) by thermolysis of p-toluenesulfonyl hydrazide (TSH). The HLNR structure was characterized by Fourier-transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies. Thermogravimetric analysis (TGA) showed that the HLNR had higher decomposition temperature compared to LNR. A response surface methodology (RSM) based on a central composite rotatable design (CCRD) with five-level-three-factors was used to opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It ultimately governs the mechanical properties, durability, spectral stability, shelf lives, and life cycles of polymers. Many investigations prepared the hydrogenation of different materials such as ENR, , liquid epoxidized natural rubber, NR, and liquid natural rubber . They reported that the thermal stability of hydrogenated products was improved by a decomposition temperature shift to a higher temperature than the original polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It ultimately governs the mechanical properties, durability, spectral stability, shelf lives, and life cycles of polymers. Many investigations prepared the hydrogenation of different materials such as ENR, , liquid epoxidized natural rubber, NR, and liquid natural rubber . They reported that the thermal stability of hydrogenated products was improved by a decomposition temperature shift to a higher temperature than the original polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations prepared the hydrogenation of different materials such as ENR, 19 , 20 liquid epoxidized natural rubber, 21 NR, 22 and liquid natural rubber. 23 They reported that the thermal stability of hydrogenated products was improved by a decomposition temperature shift to a higher temperature than the original polymer. Decreasing the double bond decreased the weak point to be attacked by oxygen, which caused a thermooxidative reaction.…”
Section: Introductionmentioning
confidence: 99%